GURU ASLI VS GURU AI DALAM PEMBELAJARAN DI ERA DIGITAL - Suharso, Pudjo; Sedyati, Retno Ngesti; Purwatiningsih, Ary (Prosiding Temu Ilmiah Nasional Guru, 2023)
In the digital era, often referred to as Society 4.0, the learning process not only relieson advances in information technology but also witnesses intriguing phenomena. In severalcountries, such as Japan and Sweden, the learning process involves AI (Artificial Intelligence)robots that assist in teaching students. In Indonesia, AI robot teachers, specifically lecturers atPresident University, Jakarta, have already become a reality. With the progression of time andadvancements in information technology, it is conceivable that the future will see an increase inthe prevalence of AI robot teachers. The question arises: Will the presence of these AI robotsreplace human teachers in the learning process? The objective of this paper is to analyze thepotential impact of AI robot teachers compared to real teachers. The method employed is aliterature study, wherein researchers examined various writings on the subject published inreputable journals and analyzed them through content analysis. The research results indicate thatthe presence of AI robot teachers remains a complex issue. In addition to the fact that AItechnology itself has not yet demonstrated reliable development, the introduction of AI robotteachers poses challenges in a humanistic context.